Banking Sector Reforms: Rationale, Efficacy and Agenda for Third Reforms - Uppal, R. K.; Kaur, Rimpi (Indian Journal of Marketing, 2007)
An economy of a country cannot be successful till it adapts the changing environment. To line up with the changing environment, every country makes its own economic policy and India is not the exception. New economic policy (LPG) is responsible to change the economic environment in India also. To meet these dynamic changes, economic structure in the form of finance, money and capital market, is changing time-to-time and banking is one of them. Before the economic reforms, there were so many deficiencies, rigidities in the Indian economy. The financial sector of India was on the crossroads. To remove the severe crises of 1991 and to improve the performance of the Indian commercial banks, first banking sector reforms were introduced in 1991 and after their success government gave much importance to the second phase of the reforms in 1998. After the gap of six years, now it has become imperative to modify some of the old reforms and introduced some new reforms in the global age. Suggested third phase of reforms will help to strengthen the ongoing economic reforms.In the present paper, an attempt is made to review the first and second reforms, their necessity and efficacy. The paper analyzes, should India reform the banking sector reforms or to what extent? On the basis of their efficacy, the present paper suggests some new reforms, which will strengthen the ongoing banking sector reforms and ultimately to the economic reforms.